From Polymeric Nanoformulations to Polyphenols-Strategies for Enhancing the Efficacy and Drug Delivery of Gentamicin - Ance Bārzdiņa; Aiva Plotniece; Arkadij Sobolev; Karlis Pajuste; Dace Bandere; Agnese Brangule (MDPI AG, 2024)
Gentamicin is an essential broad-spectrum aminoglycoside antibiotic that is used in over 40 clinical conditions and has shown activity against a wide range of nosocomial, biofilm-forming, multi-drug resistant bacteria. Nevertheless, the low cellular penetration and serious side effects of gentamicin, as well as the fear of the development of antibacterial resistance, has led to a search for ways to circumvent these obstacles. This review provides an overview of the chemical and pharmacological properties of gentamicin and offers six different strategies (the isolation of specific types of gentamicin, encapsulation in polymeric nanoparticles, hydrophobization of the gentamicin molecule, and combinations of gentamicin with other antibiotics, polyphenols, and natural products) that aim to enhance the drug delivery and antibacterial activity of gentamicin. In addition, factors influencing the synthesis of gentamicin-loaded polymeric (poly (lactic-co-glycolic acid) (PLGA) and chitosan) nanoparticles and the methods used in drug release studies are discussed. Potential research directions and future perspectives for gentamicin-loaded drug delivery systems are given.